What is the cost of delivering routine vaccinations at GP practices in England? A comparative time-driven activity-based costing analysis - Tim Crocker-Buque; Kitty Mohan; Mary Ramsay; Michael Edelstein; Sandra Mounier-Jack (Human Vaccines & Immunotherapeutics, 2019)
Background: The expansion of available vaccines in recent years has increased the overall costs of the vaccine program and put pressure on providers responsible for vaccination. In England in 2016–17, GP practices responsible for vaccinating their local population were paid £227 million. However, the costs to general practice of delivering the program and the factors influencing these costs are unknown. Therefore, the aim of this study was to evaluate the costs of delivering the routine vaccination program at GP practices in England, to identify organizational factors impacting costs, and to compare these to the funding received. Methods: Time Driven Activity Based Costing was undertaken at a convenience sample of nine geographically and socio-economically diverse GP practices in 2017–2018. Cost data were gathered for the preceding year using a survey and clinical and administrative staff kept activity logs for a 2-week period. Results: The mean cost of delivering a childhood vaccination appointment was £18.20 (range £9.71-£25.97) and an adult appointment cost £14.05 (range £7.59-£20.88), of which 75% was for staff, 24% for facility costs and 1% for consumables. Organizational factors contributing to lower costs include: shorter length of allocated appointment; greater use of administrative and reception staff; lower working time for practice manager and practice nurse; and use of health-care assistants for adult vaccinations. The costs identified are lower than payments at all practices. Conclusions: Funding received for vaccination activities was higher than costs at included practices. Several organizational factors have been identified that impact on program delivery costs that could be modified.